Cognitive impairment indicator for the neuropsychological test batteries in the Canadian Longitudinal Study on Aging: definition and evidence for validity - O’Connell, Megan E.; Kadlec, Helena; Griffith, Lauren E.; Wolfson, Christina; Maimon, Geva; Taler, Vanessa; Kirkland, Susan; Raina, Parminder (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Prevalence of overall cognitive impairment based on each participant’s performance across a neuropsychological battery is challenging; consequently, we define and validate a dichotomous cognitive impairment/no cognitive indicator (CII) using a neuropsychological battery administered in a population-based study. This CII approximates the clinical practice of interpretation across a neuropsychological battery and can be applied to any neuropsychological dataset. Methods Using data from participants aged 45–85 in the Canadian Longitudinal Study on Aging receiving a telephone-administered neuropsychological battery (Tracking, N = 21,241) or a longer in-person battery (Comprehensive, N = 30,097), impairment was determined for each neuropsychological test based on comparison with normative data. We adjusted for the joint probability of abnormally low scores on multiple neuropsychological tests using baserates of low scores demonstrated in the normative samples and created a dichotomous CII (i.e., cognitive impairment vs no cognitive impairment). Convergent and discriminant validity of the CII were assessed with logistic regression analyses. Results Using the CII, the prevalence of cognitive impairment was 4.3% in the Tracking and 5.0% in the Comprehensive cohorts. The CII demonstrated strong convergent and discriminant validity. Conclusions The approach for the CII is a feasible method to identify participants who demonstrate cognitive impairment on a battery of tests. These methods can be applied in other epidemiological studies that use neuropsychological batteries.